A novel association between the grass pest Argentine stem weevil (Coleoptera: Curculionidae) and peas. Issue 3 (2nd July 2020) - McNeill, Mark R.; Scott, Ralph E.; Richards, Nicola K.
ABSTRACT: Argentine stem weevil ( Listronotus bonariensis ) has been confirmed as infesting spring sown pea seedlings drilled on 22 October 2016 on a Canterbury farm. Infestations were observed in two neighbouring paddocks, with a visual estimate of 7–10% of the plants damaged in the worst affected areas. Symptoms included wilting and yellowing of new growth. Visual inspection of infested plants found entry and exit points, mining of the stem and a single larva per seedling. Amplification of mitochondrial barcodes of four larvae collected from individual plants provided a 100% match to L. bonariensis. The peas had been direct drilled into a nil-endophyte Italian ryegrass ( Lolium multiflorum ) stand that had been treated with herbicide to kill the vegetation but not treated with insecticide before or when the peas were planted, and it is likely larvae have transferred from the dying grass to infest the seedlings. Listronotus bonariensis eggs were also found on one of the plants collected from the paddock on 18 November 2016. This is a new host plant record for L. bonariensis, and while considered a specific pest of grasses, adults will feed on seedling brassicas.